Renal Cyclooxygenase Products are Higher and Lipoxygenase Products are Lower in Early Disease in the pcy Mouse Model of Adolescent Nephronophthisis. Issue 1 (1st November 2013) - Yamaguchi, Tamio; Lysecki, Clara; Reid, Ashleigh; Nagao, Shizuko; Aukema, Harold M.
Abstract: Nephronophthisis (NPHP) is a pediatric form of hereditary polycystic kidney disease (PKD), and is the leading cause of end stage renal disease in children. The pcy mouse is an orthologous model of human NPHP, with a mutation in the Nphp3 gene. Renal phospholipase A2, cyclooxygenase (COX) 1 and cyclic AMP are elevated in this model, suggesting that eicosanoid formation may be altered. In another type of PKD observed in the Han:SPRD‐ Cy rat, inhibition of eicosanoid production slows disease progression. If renal eicosanoids are similarly altered in NPHP, potential for pharmacologic intervention also may exist for this disorder. Therefore, renal fatty acids and eicosanoids were determined in pcy and normal mice at 15, 30 and 60 days of age by gas chromatography and HPLC–tandem mass spectrometry, respectively. Renal cysts in enlarged kidneys were observed in pcy mice by 15 days of age and increased over time. Renal phospholipid ARA levels were higher in pcy compared to normal mice at 15 and 30 days. Eicosanoid differences were observed starting at 30 days, when the COX products 6‐keto‐prostaglandin (PG) F1α, thromboxane B2 and PGE2 were higher in pcy compared to normal kidneys. Overall, total COX products were elevated at 30 and 60 days. In contrast, the levels of the lipoxygenase (LOX) products were not altered until 60 days of age and these were lower in pcy kidneys compared to normal. These findings suggest that altered eicosanoids play a role in NPHP, and that manipulating these levels with pharmacologic agents may have therapeutic potential.